Severe falciparum malaria and peripheral gangrene - Ibrahim SMA; Harunarashid H (Department of Surgery, UKM Medical Centre, 2011)
Patients with Falciparum malaria may present with peripheral gangrene as a rare complication. In this report we describe two adult Sudanese patients with high grade fever for 10 days, jaundice, alteration consciousness and hypovolaemic shock. Both patients had blackish discolouration of the fore foot and the toes, bilaterally. Blood smears showed hyperparacitaemia with Plasmodium falciparum. They were diagnosed as having severe malaria with peripheral gangrene; they were treated with quinine infusion and the foot lesions recovered spontaneously without surgical intervention